Strengthening multi-stakeholders innovations platforms in Mali - Dossou-Yovo, Elliott Ronald; Guindo, Jonathan; Koné, Pierre; Doumbia, Salif (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Most of the smallholder farmers in Mali are confronted with multifaceted challenges, which include low productivity, post-harvest crop losses, underdeveloped markets, vulnerability to climate change, and gender inequality affecting the distribution of resources. These problems require interventions such as institutional reforms that facilitate efficient rural service delivery, development of markets, creation of physical infrastructure, and supportive government policies while ensuring a stable and conducive political environment. In an attempt to enable discussions, negotiations, and joint planning between stakeholders from the rice-based systems, AICCRA-Mali established multi-stakeholders platforms (MSP) in the inland valley sites of Finkolo Ganadougou, Blendio, and Loutana in Sikasso, southern Mali, identified capacity building needs, and conducted training sessions to strengthen the capacity of MSP actors for optimal and sustainable performance. MSP actors were dealing with issues such as a lack of input, information, and finance, as well as competing for the use of inland valley resources. Based on needs assessments, training in contract farming, trust building, and consensus building over the use of multiple inland valley resources was provided to the MSP actors, and indicators for monitoring the performance of the MSPs were defined by the actors. The framework used in this report can be employed to inform planning and adaptive management, demonstrate performance, and inform the design of new interventions in MSPs.